2013
DOI: 10.4028/www.scientific.net/kem.554-557.195
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Incremental Forming of Titanium F67 Grade 2 Sheet

Abstract: Analysis of a formed metal sheet shows the data of the incremental forming process. Variation in sheet deformation results from the process and shows how forming occurred. Another important result is the surface roughness of the sheet, which reports the parameters of the process, machine and tool used. Incremental forming of the titanium CP-Ti grade 2 sheet was performed in the SPIF modality – forming without a point of support, in order to look at the thickness deformations. SPIF incremental forming is charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…Gatea et al 14 carried out the experimental and FE analysis for ISF process to evaluate the impact of step down, feed rate and tool diameter on formability of titanium grade and grade 2 using GTN damage model. Daleffe et al 15 have analysed ISF of CP-Ti Grade-2 at room temperature and showed that the limit wall angle for the CP-Ti grade 2 sheet of 0.5 mm thickness is 47°. Literature reports that heating during forming process can improve the process performance as it increases formability, improves dimensional accuracy, and reduces forming forces.…”
Section: Introductionmentioning
confidence: 99%
“…Gatea et al 14 carried out the experimental and FE analysis for ISF process to evaluate the impact of step down, feed rate and tool diameter on formability of titanium grade and grade 2 using GTN damage model. Daleffe et al 15 have analysed ISF of CP-Ti Grade-2 at room temperature and showed that the limit wall angle for the CP-Ti grade 2 sheet of 0.5 mm thickness is 47°. Literature reports that heating during forming process can improve the process performance as it increases formability, improves dimensional accuracy, and reduces forming forces.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the surface quality deteriorated by increasing the forming angle. Titanium F67 grade 2 sheet for medical implant was formed by SPIF, and internal and external roughness was measured by Daleffe et al [89]. The roughness of three sheets was measured with a changing angle of 45°, 47°a nd 48°.…”
Section: Forming Anglementioning
confidence: 99%
“…Because of their formability properties and light weight, the brass and copper are two materials frequently used for ISF process [24,25]. Titanium alloys well-known for their corrosion resistance and high strength and magnesium alloys for their light weight are used in many industries, thus the parts can be also obtained using incremental forming processes [26,27]. A lot of components from all the industries are made from steel sheets and its derivates, thus these materials are investigated if it is possible to be formed with ISF process, especially cold presing steel like deep drawing and extra deep drawind steel [24,28] There are research to evaluate the possibility to incremental deform the polymer sheets, for a low volume with a low cost production [29].…”
Section: Methodsmentioning
confidence: 99%